Trophic ecology of the intertidal sea anemone Bunodosoma zamponii (cnidaria, actiniaria): Diet composition, seasonal variation and trophic parameters - Erralde, Stefanía Micaela (2020)
Sea anemones are considered as polyphagous opportunistic predators and it has been suggested that their diet reflects the structure of the community they inhabit. The feeding ecology of intertidal species is an interesting topic to study due to their wide variety of strategies to obtain food. In this sense, we studied the diet of Bunodosoma zamponii, the most abundant actiniarian in the rocky intertidal of Punta Cantera (Mar del Plata, Argentina). The objectives were to describe it and compare its composition seasonally and between diurnal and nocturnal high tides. We examined the gastric cavity content of 154 specimens collected seasonally at both diurnal and nocturnal high tides, and 39 different prey items were identified, some of which are recorded here for the first time for this species. No variations on diet composition were found between seasons or between diurnal and nocturnal high tides, suggesting that the food available does not vary either. Bunodosoma zamponii ingests mostly items with low biomass, which contribute to the total biomass ingested in direct proportion to their frequency in the diet. The bivalve Brachidontes rodriguezii was the main prey for the anemone, followed to a lesser extent by certain amphipods, other mollusks and algae.